2017
DOI: 10.1589/jpts.29.1658
|View full text |Cite
|
Sign up to set email alerts
|

H-reflex changes in adolescents with idiopathic scoliosis: a randomized clinical trial

Abstract: [Purpose] To detect H-reflex asymmetry and investigate the effect of direction sensitive exercise therapy protocol among patients with thoracolumbar and/or lumbar scoliosis. [Subjects and Methods] Fifty patients (10–17 years), Cobb’s angle 10–20 degrees with thoracolumbar and lumbar scoliosis participated in the study. Soleus H-reflex was tested on both sides during prone lying position and standing position. Patients were randomly assigned into two groups. Group I received direction sensitive exercise therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…One study [22] included in this review compared a strict bracing regimen with SSE, and reported that bracing was more effective than SSE in reducing curve progression, with lower mean spinal deformity measures at follow-up reported for bracing. This is supported by evidence from previous reviews [1,4,7,[30][31][32][33][34][35] of observational and controlled studies showing improvements in Cobb angle measurements with bracing. However, the results of the meta-analysis revealed a mean difference between groups of 2.7°, which is below the normally accepted MDC of 6° [25].…”
Section: <B>sse Vs Bracingsupporting
confidence: 80%
“…One study [22] included in this review compared a strict bracing regimen with SSE, and reported that bracing was more effective than SSE in reducing curve progression, with lower mean spinal deformity measures at follow-up reported for bracing. This is supported by evidence from previous reviews [1,4,7,[30][31][32][33][34][35] of observational and controlled studies showing improvements in Cobb angle measurements with bracing. However, the results of the meta-analysis revealed a mean difference between groups of 2.7°, which is below the normally accepted MDC of 6° [25].…”
Section: <B>sse Vs Bracingsupporting
confidence: 80%
“…If the curvature of the Cobb angle of 10° and above shows an increase by 5° and more within six months, it is progressive (Sarwark & Davis, 2018;Kanter et al 2018). Information regarding the length of the scoliosis arch, the degree of rotation, torsion and vertebral wedgedness is also of importance (Alayat et al, 2017;Le Berre et al 2017). It is also recommended to assess the correctability of scoliosis, tested in the plane of maximal deformation, and bone age (the Risser test) (Minkara et al 2018;Ng & Bettany-Saltikov, 2017) .…”
Section: Introductionmentioning
confidence: 99%